A Legal Analysis of the Opportunities and Challenges of Implementing the Presidential Instruction of the Republic of Indonesia Number 1 of 2025 in the Management of the National Education Budget - Muh. Syah Quddus; Reynaldi Hermansyah; Immawan Wahyudi (Neo Journal of economy and social humanities, 2025)
Education budget management is a vital instrument in realizing the constitutional right to education and improving the quality of Indonesia's human resources. However, reality shows that disparities in allocation, weak supervision and rampant irregularities reduce the effectiveness of the budget. Presidential Instruction No. 1 of 2025 comes as a normative response to strengthen education budget governance, but its implementation cannot be separated from juridical complexities and coordinative challenges in the field. This study aims to juridically analyze the opportunities and challenges of implementing Presidential Instruction No. 1 of 2025 in education budget management in Indonesia. The method used in this research is juridical-normative research, by analyzing secondary data from primary, secondary, and tertiary legal materials. The results show that Presidential Instruction Number 1 Year 2025 has great potential in improving the efficiency and equity of education budget management in Indonesia. However, its implementation faces serious legal challenges, especially related to the unsynchronized regulations between the center and the regions and weak supervision. Therefore, continuous legal reforms, improved regional managerial capacity and a more integrated monitoring system are needed to support the effectiveness of this policy